Aktivitas Antivirus Polifenol sebagai Profilaksis dan Terapi Potensial dalam Penanganan Covid-19 - Teddy Tjahyanto; Eldy Eldy; Clarissa Felicia; Karmenia Jessica Karmenia Jessica; Olivia Larissa (Syntax Corporation Indonesia, 2022)
COVID-19 has caused serious health problems worldwide. Until now, the available therapy hasn’t been fully effective in improving outcomes in COVID-19 patients. Due to the long process of discovering new drugs, the use of available treatment becomes a solution. However, this therapy has several drawbacks, such as decreased effectiveness in mutated viruses and various serious side effects that accompany it. Polyphenols can be considered as adjunctive therapy for COVID-19 because of their rich variety and antiviral activities. This literature review was conducted to summarize the latest evidence regarding the potential antiviral activity of polyphenols as both prophylactic and therapeutic for COVID-19, as well as further discussion on encouragement of polyphenol intake from diets and recommended food examples. Literature sources were taken from journal articles published online from 2017 to 2021. The databases used were MDPI, PubMed, ScienceDirect, Wiley, and Hindawi. Research shows the use of polyphenolic compounds has been approved as a beneficial nutritional or adjunctive therapeutic approach for COVID-19. This is based on the role of polyphenol bioactivity in the pathophysiology of COVID-19, including antioxidant, antiviral, anti-inflammatory, and immunomodulatory effects. Additional studies that specifically examine the administration of polyphenols to pregnant COVID-19 patients and dose safety limits related to interactions with drugs used in the treatment of COVID-19 need to be conducted.